Pré-tratamento de resíduos agroindustriais com enzimas ligninolíticas para produção de bioetanol - Matei, Jéssica Crecencio (2018)
In 2017 approximately 515 million tons of sugarcane bagasse and 102 million tons of rice husks were produced around the world. These residues can be used for the production of second generation ethanol, as the cellulose present in the composition of both can be hydrolyzed and then fermented. However, a treatment in the biomass is necessary to reduce the present lignin barrier, without generating toxic components. In this way, the objective of this work was to evaluate the application of a biological pretreatment with enzymatic extracts produced by white rot fungi, in sugarcane bagasse and rice husk, for saccharification and fermentation. The fungi studied were: Trametes sp., Pleurotus pulmonarius, Ganoderma lucidum, Inonotus splitgerberi, Perenniporia sp. and Aurantioporus pulcherrimus. The production of enzymatic extracts was carried out in a nutrient medium incorporated of natural inducers of ligninolytic enzymes (rice husk or sugarcane bagasse). The cultures were incubated at 28°C in static condition for 7 days and the activity of the enzymes was determined by colorimetric analysis. The best results were obtained by Trametes sp., with a maximum activity of 9.467,8 U/L of laccase produced in the presence of sugarcane, and Pleurotus pulmonarius, which presented 5.099,9 U/L of this enzyme with rice husk. Subsequently, the enzymatic extracts obtained by Trametes sp., containing laccase as the main ligninolytic enzyme, were applied to cane or rice wastes together with other factors (hydroxybenzotriazole, Tween 80, sodium acetate buffer, hydrogen peroxide, 2,6-dimethoxyphenol and 4-hydroxybenzoic acid) in a treatment at 28°C, 48 hour under stirring at 130 rpm. Then, the products from the pre treatment were saccharified, for 72 hours at 50°C, with the enzymatic cocktail Cellic Ctec2 (Novozymes). The determination of saccharides was performed by 3,5- dinitrosalicyclic acid. The enzymatic treatment containing all factors resulted in 0.22 g/L and 0.30 g/L of sugars, in sugarcane bagasse and rice husk, respectively, corresponding to at least double the value of the control (treated only with boiling water). In this same treatment, the saccharification increased the sugar concentration by more than 9 times when compared to the control, resulting in 4.07 g/L sugars in the cane substrate and 3.39 g/L in the rice residue. Fermentation with cane hydrolyzate was performed at 28°C during 36 hours for two isolates of Saccharomyces cerevisiae. The yields observed were 5.30 and 4.64 grams of sugar per gram of ethanol, with a productivity around 0.5 g/(L.h), yielding 18.62 and 16.02 g/L of the alcohol at the fermentation process end.